2007
DOI: 10.1097/01.nna.0000285112.14948.0f
|View full text |Cite
|
Sign up to set email alerts
|

Postbaccalaureate Nurse Residency 1-Year Outcomes

Abstract: The authors document the 1-year outcomes of the postbaccalaureate residency program jointly developed and implemented by the University Health-System Consortium and the American Association of Colleges of Nursing. Data on 2 cohorts of residents (n = 679) in 12 sites across the country are presented. The 1-year termination rate was 12%, after those lost to the program because of National Council Licensure Examination failure, serious illness, or death were eliminated from the analysis. Additional analyses using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 11 publications
8
92
1
Order By: Relevance
“…This study adds to the growing body of evidence that demonstrates the efficacy of transition to practice programs (Beecroft et al, 2007;Beyea, von Reyn, & Slattery, 2007;Fink, Krugman, Casey & Goode, 2008;Goode et al, 2009;Salt, Cummings, & Profetto-McGrath, 2008;Williams, Goode, Krsek, Bednash & Lynn, 2007). In this study it was apparent that nurses who were fully invested in the program had better outcomes than those who were not.…”
Section: Support For Transition To Practice Programsmentioning
confidence: 48%
“…This study adds to the growing body of evidence that demonstrates the efficacy of transition to practice programs (Beecroft et al, 2007;Beyea, von Reyn, & Slattery, 2007;Fink, Krugman, Casey & Goode, 2008;Goode et al, 2009;Salt, Cummings, & Profetto-McGrath, 2008;Williams, Goode, Krsek, Bednash & Lynn, 2007). In this study it was apparent that nurses who were fully invested in the program had better outcomes than those who were not.…”
Section: Support For Transition To Practice Programsmentioning
confidence: 48%
“…A turnover rate of 8% was reported, full details reported in Beecroft et al Williams et al 26 conducted a longitudinal, descriptive study to evaluate one year outcomes of a Post-Baccalaureate Nurse residency. A total of 679 nurse residents from 2 cohorts: alpha (n=486) and beta (n=193) who completed the programme were included in the study.…”
Section: Clinical Orientation/inductionmentioning
confidence: 99%
“…Altier and Kresk, 53 carried out a prospective, longitudinal study to evaluate the effect of a one year post baccalaureate nurse residency program, using a standardised curriculum, upon job satisfaction and retention of (n=316) baccalaureate-prepared graduates in their first year of employment. Although not specifically stated this study pilot tested the residency programme reported by 26,[54][55][56] . There was an overall response rate of 35%, with 111 out of 316 having complete data at both baseline and follow up which was included in the analysis.…”
Section: University Hospital Consortium/american Association Of Collementioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][28] An internship program of Children's Memorial Hospital in Chicago that included classroom and skills lab learning, precepted orientation, professional transitioning sessions, and clinical learning exchanges contributed to increasing nursing recruitment and retention, significant cost savings, and increasing nursing satisfaction. [29,30] In another study of one-year outcomes of a post-baccalaureate residency program, Williams and colleagues [31] found that participants' job satisfaction improved on study variables such as, professional opportunities and control-responsibility at 12 months. Bratt and colleagues [12] also claimed that perceptions of the work environment particularly job satisfaction and job stress were found to be most influential.…”
Section: Literature Reviewmentioning
confidence: 99%